2003
DOI: 10.1093/emboj/cdg381
|View full text |Cite
|
Sign up to set email alerts
|

NFAT functions as a working memory of Ca2+ signals in decoding Ca2+ oscillation

Abstract: Transcription by the nuclear factor of activated T cells (NFAT) is regulated by the frequency of Ca 2+ oscillation. However, why and how Ca 2+ oscillation regulates NFAT activity remain elusive. NFAT is dephosphorylated by Ca 2+ -dependent phosphatase calcineurin and translocates from the cytoplasm to the nucleus to initiate transcription. We analyzed the kinetics of dephosphorylation and translocation of NFAT. We show that Ca 2+ -dependent dephosphorylation proceeds rapidly, while the rephosphorylation and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
221
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(251 citation statements)
references
References 29 publications
26
221
1
Order By: Relevance
“…We note that calcium sensors are often highly sensitive to the pattern of calcium concentration changes in the cytosol; rapid calcium oscillations are seen to activate NF-kB, NFAT and Oct/OAP, while only NFAT responds to slower oscillations. 122,123 Could calcium sensors that affect actin dynamics and cellular contractility be similarly sensitive to patterns of intracellular calcium concentration changes? Clearly dissecting the role of calcium influxes in epithelial scattering will prove complex if such is the case.…”
Section: Discussionmentioning
confidence: 99%
“…We note that calcium sensors are often highly sensitive to the pattern of calcium concentration changes in the cytosol; rapid calcium oscillations are seen to activate NF-kB, NFAT and Oct/OAP, while only NFAT responds to slower oscillations. 122,123 Could calcium sensors that affect actin dynamics and cellular contractility be similarly sensitive to patterns of intracellular calcium concentration changes? Clearly dissecting the role of calcium influxes in epithelial scattering will prove complex if such is the case.…”
Section: Discussionmentioning
confidence: 99%
“…Provocatively, altered NFAT function in mice through genetic ablation gives rise to valvulogenesis defects (23,24) that bear some similarity to the congenital heart defects observed in a mouse model of Noonan syndrome (12). There is good evidence that calcineurin which activates NFAT by dephosphorylation is regulated not just by increases in intracellular Ca 2ϩ but also by the oscillatory frequency of Ca 2ϩ (27). After NFAT translocation to the nucleus, it also has been shown that NFAT transcriptional activity is modulated by the frequency of intracellular Ca 2ϩ oscillations (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…We recorded Ca 2ϩ sparklets, [Ca 2ϩ ] i , and nuclear NFATc3 translocation in primary cultured human aortic smooth muscle cells expressing NFATc3 tagged with EGFP (17,18) (Fig. 5).…”
Section: Pkc-induced Local Ca 2؉ Signals Via Ltccs Activate Nfatc3 Anmentioning
confidence: 99%